A Kit to Facilitate and Standardize the Processing of Sputum for Measurements of Airway Inflammation. Issue 4 (2013) - Chaboillez, Simone; Dasgupta, Angira; Prince, Philippe; Boulet, Louis-Philippe; Lemière, Catherine
Abstract : BACKGROUND: The use of inflammometry has been shown to be effective for managing asthma. However, sputum processing can be time consuming. Furthermore, methods of sputum processing can vary among facilities. To help with standardization and to simplify the procedure for laboratory staff, a novel, commercially available processing device (Accufilter, Cellometrics Inc, Canada) has been developed. OBJECTIVE: To assess the validity of the Accufilter device and kit for recovery of treated specimens, and for quantitative sputum inflammatory cell counts by comparing intrasample measurements with those using the same procedure without the Accufilter device and kit. METHODS: The present study was a wet laboratory comparison of induced sputum cell counts obtained from sputum processed with versus without the device and kit. Comparisons of each sputum specimen were performed by the same technologist in random order. RESULTS: A total of 39 samples were processed using both the standard method and the Accufilter device. The intraclass correlation coefficients were high for the weight of the filtrate, and for eosinophil and neutrophil differential counts. CONCLUSION: A good degree of agreement of results was apparent when the two methods were compared. The differences noted between both methods were minimal and did not modify clinical interpretation. The use of the Accufilter device and kit can be used in place of the standard method for sputum quantitative analysis, especially in centres with large sample loads.